What Factors Influence the Survival of Subsidised Start-ups for the Unemployed in Slovakia? - Peter Pisár; Alexandra Mertinková; Miroslav Šipikal (Central European Public Administration Review)
Purpose: The aim of the paper is to analyse the factors of sustainability of the public policy subsidising start-ups for the unemployed in Slovakia. Design/Methodology/Approach: The analysis assesses the sustainability of subsidies in the period 2012-2016 based on data provided by the Ministry of Labour and Social Affairs. Logistic regression was used to identify the key factors. Findings: Research shows that in times of economic growth, policies to support the self-employment of the unemployed are a particularly effective form of active labour market policy, especially in the more developed regions. On the contrary, when serving as a business support tool, they lead to very low survival rates of the subsidised companies compared to results of other studies. In terms of factors affecting this sustainability, the length of unemployment, the amount of support, as well as regional characteristics emerge as the most significant. Practical implications: The results allow for a better definition of the conditions for providing subsidies to the unemployed to start a business in the future, while also showing that this instrument leads to employment retention rather than to the promotion of entrepreneurial activities. Originality/value: The research was carried out under specific conditions that had been little explored so far. The policy was evaluated at a time of strong economic growth accompanied by a significant reduction in unemployment. Also worth noting is that it was carried out in a country with some of the most pronounced regional disparities, which made it possible to compare the impact of the policy in different starting conditions.